Efeitos da exposição à nanopartícula de dióxido de titânio em diferentes pH do meio aquático em brânquias de curimbatá (Prochilodus lineatus, Teleostei, Prochilodontidae) : aspectos bioquímicos, fisiológicos e morfofuncionais - Souza, Naiara Elisabete da Silva de (Universidade Federal de São Carlos, 2015)
The titanium dioxide nanoparticles (NP-TiO2) has achieved into aquatic ecosystems through different sources, such as sewer and leaching. Abiotic factors such as pH, ionic strength, water hardness may change the chemical aggregation of NPs as well as the bioavailability of metals in waters result of speciation and /or complexation with other compounds. Considering the pH variations can occur in the environment naturally or as a result of ecological accidents and the increasing use of NP-TiO2 in many different industries, this study aimed to determine the CL-50; 48 hours of NPTiO2 in different pH (acidic, neutral and basic) in juvenile Prochilodus lineatus (curimbatá) and evaluating the effects of exposure to sublethal NP-TiO2 these pH using biochemical, physiological and morphological biomarkers. After sensitivity test with KCl, the animals were tested with different concentrations of NP-TiO2 at pH 5.0, 7.0 and 8.0 for 48 hours to determine the CL-50; 48h. Subsequently, the animals were exposed to 1 mg L-1 NP-TiO2 for 48 hours at different pH. After the exposure period, blood samples were obtained via caudal puncture for ion plasma analysis and hematologic variables, and samples of gills were collected and fixed. The analytical characterization of NP-TiO2 suggest the aggregation ability are modified of the NP at different pH and at pH 5.0, the hydrodynamic diameter of the NP is much larger then the others pH, which may have create difficults for the entry of NP in organisms and caused less damage. The NP-TiO2 were considered non-toxic in pH 5,0, 7,0 and 8,0. Exposure to NP-TiO2 pH 5.0 and ionic imbalance caused in the exposed animals, possibly due to changes in the concentration of Cl- ions. Exposure to pH 5.0 and 8.0 and NP-TiO2 at pH 7.0 inhibited AC enzyme. In animals exposed to NP at pH 5.0 were not identified cloride cells with crypt surface, possibly due the blocking of these surfaces by the large NP aggregates. Changes in concentrations of ROS and SOD, CAT and GCL activity may indicate an imbalance in antioxidant system due to different pH and NPTiO2 exposure. NP exposure caused major damage at pH 7.0, where have lower hydrodynamic diameter , supporting the hypothesis that the smaller the size of the cluster,it’s easier the NP enter the body of the exposed animals.
Keywords: Nanopartícula de dióxido de titânio; Diferentes pH; Brânquias; Prochilodus lineatus; Gills; Titanium dioxide nanoparticles; Different pH; CIENCIAS BIOLOGICAS::FISIOLOGIA